The Prevalence of Overweight and Obesity in Iranian Men; a Systematic Review and Meta-Analysis Study - Hosseini, Jalil; Nematollahi, Shahrzad; Shariatpanahi, Samira; Sadegh-Zadeh, Zahra (Archives of Men's Health, 2021)
Introduction: Overweight and obesity is one of the most common diseases worldwide that is less considered in men. In this regard scattered studies have been conducted in Iran, and our aim was to systematically study the prevalence of overweight and obesity in Iranian men. Methods: Major international databases including: Scopus and PubMed, and Web of Science and national databases including Magiran and SID were searched for articles in Persian and English which were published from August 10, 2010 to August 10, 2020. Qualitative evaluation of the studies was performed using the Newcastle-Ottawa Scale checklist (NOS). Random effects model was used to estimate the pooled prevalence by STATA software version 14.2 with significance level of 0.05. Results: Overall, 52 studies with a total sample size of 120,440 men with age range of 20-77 years were included in this systematic review. Most studies were conducted in 2017 and almost all of them were in Tehran province. The pooled prevalence of overweight was 46% (95% CI: 46, 46) in men. The lowest prevalence of overweight was 11.1% in Fars and the highest was 57% in Tabriz. The pooled prevalence of obesity in men was 18% (95% CI: 18, 19) with the highest prevalence in Birjand (46.5%) and the lowest in Tehran (0.8%). Conclusion: Our results showed a variety of tools for measuring overweight and obesity in Iran. Based on the BMI index, we found that the prevalence of overweight and obesity was substantial among Iranian men. There seems to be an urgent need for health policy makers to develop and implement proper preventive strategies in order to control this public health problem and its serious health consequences among men, especially in the workplace.